Esophageal Plasmacytoma Revealed by Persistent Hiccups: A Case Report and Literature Review - Khaoula Khalil; Fatima Ezzahra Lahlimi; Illias Tazi (Case Reports in Gastrointestinal Medicine)
Introduction. Solitary extramedullary plasmacytoma (SEP) is a rare neoplasm that is derived from monoclonal proliferation of plasma cells in the soft tissues or organs arising outside the bone marrow. It is present in about 3% of all plasma cell tumors and originates mainly from the upper respiratory tract and nasopharynx. Involvement of the esophagus is exceptionally seen in cases of SEP. Case Presentation. We report a novel case of a 74-year-old male patient attended with a 6-month history of hiccupping further associated with dysphasia and weight loss all caused by esophageal plasmacytoma. Histological and immunohistochemical examination of the tumor confirmed the diagnosis of plasmacytoma. Workup for the multiple myeloma came out to be negative, thus confirming the diagnosis of SEP. The patient was treated with radiotherapy alone, leading to complete remission (at 30 months of follow-up). Conclusion. Esophageal plasmacytoma, an exceptional presentation of extramedullary plasmacytoma, should be kept in mind while dealing with patients presenting with intractable hiccups.